INSTRUCTIONAL PROCESS COMPETENCIES: AN ANALYSIS OF CLASSROOM PRACTICES IN WORKERS WELFARE MODEL SCHOOLS - Tahir Kaleem Siddiqui, Maqsood Alam Bukhari,Aftab Mughal (PJE, 2023)
This research was designed to study Instructional Process Competencies through observation of classroom practices in workers welfare model schools in Pakistan. The study was designed to identify essential teacher competencies for school effectiveness and to find out if the classroom practices used by Workers Welfare Model School teachers are consistent with these competencies. Forty sample schools were selected from a total of 75 on all Pakistan bases. The data collected through the questionnaire, classroom observations, focused group discussion and official documents was analyzed using both qualitative and quantitative techniques.